Land use and mineral type determine stability of newly formed mineral-associated organic matter - De Shorn E. Bramble; Ingo Schöning; Luise Brandt; Christian Poll; Ellen Kandeler; Susanne Ulrich; Robert Mikutta; Christian Mikutta; Whendee L. Silver; Kai Uwe Totsche; Klaus Kaiser; Marion Schrumpf (Communications Earth & Environment)
Abstract Formation of mineral-associated organic matter (MAOM) is a key process in the global carbon cycle, stabilising organic carbon in soils. The relative importance of mineral composition and land use as potential controls of MAOM stability at regional scales and underlying microbial processes are still unresolved. Here, we assessed the stability of MAOM formed on goethite (iron oxide) and illite (phyllosilicate clay) exposed for five years in topsoils at 68 forest and grassland sites across Germany. We incubated the newly formed MAOM, determined its extractability, and analysed the composition and functioning of associated microbial communities. Decomposition of MAOM was always significantly lower for goethite than illite, highlighting that higher organic carbon accumulation on goethite was not exclusively due to its larger sorption capacity. Instead, reduced organic carbon extractability and higher phosphorus-acquiring enzyme activities indicated stronger substrate limitation of microbial growth on goethite than illite. Across the two minerals, MAOM decomposition was consistently lower for forests than grasslands, relating to greater nutrient constraints and a different microbial community composition in forests. Overall, mineral type and land use explained 34.6 and 23.2% of the variance in MAOM decomposition. The pronounced land use effect on MAOM stability underlines its potential responsiveness to environmental change.